Developing Graphitic Carbon Nitride for Effective Treatment of Organic Pollutants in Industrial Water - Nursal; Hamid, Muhammadin; Saragi, Indah Revita; Dinda Amilia; Ivi Briliansi Dalimunthe (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Organic pollutants, including pesticides and industrial waste, have become a significant environmental challenge due to their persistence and difficulty in decomposition, posing serious threats to both environmental health and water quality. This issue is particularly pressing in regions like Penang, where rapid industrial development and urbanization have exacerbated water pollution. In response, various research efforts have explored potential solutions, with graphite emerging as an effective adsorbent for removing toxic compounds from water. Building on this, our study focuses on the synthesis of graphitic carbon nitride (g-C3N4), a material recognized for its high-performance photocatalytic properties. g-C3N4's unique structure and ability to harness solar energy make it a promising candidate for catalyzing the breakdown of organic pollutants into less harmful molecules. Our project aims to develop a cost-effective and scalable method for producing g-C3N4 using readily available materials, with the goal of mitigating organic pollution in Penang. Through a straightforward synthesis process, we seek to make this technology accessible for widespread adoption in water treatment practices. The successful synthesis of g-C3N4 has already been demonstrated, with the process being effectively shared with students from the School of Chemical Science at USM. While further refinements are needed to maximize results, our findings suggest that g-C3N4 can play a crucial role in reducing organic pollution and improving water quality, contributing to the long-term sustainability of Penang's environment.